A Historical Overview of Muslim Minority Identity and Positioning in the Philippines - Erasiah; Fikri Surya Pratama; Seskia; Cajuniati; Indah Khairu Ummah (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2023)
The discriminatory treatment of the Philippine Muslim minority dates back hundreds of years due to Spanish colonial politics that were highly allergic to Islam. Furthermore, minority nationality and ethnicity issues relate to national integration, class struggle, and economic dispossession. This study aims to explain the historical forces that shaped the identity of the Filipino Muslim community. The research method used is the historical research method, where the collection of research sources is done by literature study. This research analysis uses a political history approach closely related to power as a governmental tool in policymaking. The results show that the identity issues experienced by the Muslim minority in the Philippines in positioning themselves in the process of national integration are caused by several factors, such as history, religion, and the concept of the nation-state. However, in contemporary times, political and economic issues, in addition to religious issues, have emerged as new forces in the matter of Muslim identity in the Philippines.